The detection of oil spill onshore using the thermal band of landsat-8 - Dheya Uldeen K. Abbas; Loay E. George (Universitas Ahmad Dahlan, 2022)
Remote sensing is an advanced technique that can be used to detect hydrocarbons on land, and its advantages include rapid and low-cost detection. The detection of hydrocarbons on the surface is essential for environmental monitoring and the purpose of exploration. For oil and gas companies, the ability to locate hydrocarbon spill sites is important information for the success of future exploration wells. This study aimed to determine the quantities of hydrocarbons mixed with the soil as an indicator of its accumulation in the subsurface. In this paper, temperature data obtained from the landsat-8 satellite were used to determine the extent of the oil spill in the area using spatial interpolation and gradient techniques. Kriging interpolation is based on statistical models (i.e. including auto-correlation) geostatistical techniques can produce a forecast surface and also provide accurate forecasts. The results showed that there are 60 sites of thermal anomalies and temperature values are lowest and highest 23.2 oC to 91.11 oC, in the study area. Three different sites were chosen in terms of area and effect. They are located in the northern and southern Rumaila and Zubair fields. The location of the oil spills was determined with high accuracy after identifying the anomalies.